PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMENPADA DAPURUMA DI MASJID RAYA BINTARO JAYA TANGERANG SELATAN - Ahyani Ahyani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purposes of this study were 1) To determine the effect of product quality on consumer satisfaction at the Dapuruma at the Great Mosque of Bintaro Jaya 2) To determine the effect of service quality on consumer satisfaction at the Dapuruma at the Masjid Raya Bintaro Jaya 3) To determine the effect of product quality and service quality on satisfaction. consumers at Dapuruma At Masjid Raya Bintaro Jaya The method used is quantitative. The sampling technique used the Slovin formula and the sample obtained in this study amounted to 96 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are product quality has a significant effect on consumer satisfaction with the regression equation Y = 13,967 + 0.412X1, the correlation value of 0.654 means that the two variables have a strong relationship level. The value of the coefficient of determination is 42.8%. Hypothesis test obtained t count > t table or (8,380 > 1,986). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant effect of product quality on consumer satisfaction. Service quality has a significant effect on customer satisfaction with the regression equation Y = 14,328 + 0.648 X2, the correlation value of 0.663 means that the two variables have a strong relationship level. The value of the coefficient of determination is 44.0%. Hypothesis test obtained t count > t table or (8,596 > 1,986). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of service quality on customer satisfaction. Product quality and service quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 7.823 + 0.254X1 + 0.416X2. The correlation value of 0.739 means that the independent variable and the dependent variable have a strong relationship. The coefficient of determination is 54.6% while the remaining 45.4% is influenced by other factors. Hypothesis testing is obtained by the calculated F value > F table or (55,845 > 2,700). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect of product quality and service quality on consumer satisfaction.